Nitrogen deficiency regulates premature senescence by modulating flag leaf function, ROS homeostasis, and intercellular sugar concentration in rice during grain filling - Shamsu Ado Zakari (SpringerOpen, 2021)
Abstract Background Leaf senescence occurs in an age-dependent manner, but the rate and timing of leaf senescence may be influenced by various biotic and abiotic factors. In the course of stress, the function, composition, and different components of photosynthetic apparatus occur to be synthesized homogeneously or degraded paradoxically due to different senescence-related processes. Nitrogen (N) deficiency is one of the critical environmental factors that induce leaf senescence, and its incidence may curtail leaf photosynthetic function and markedly alter the genetic information of plants that might result in low grain yield. However, the physiological and genetic mechanism underlying N deficiency regulates premature senescence, and flag leaf function, ROS homeostasis, and intercellular sugar concentration in rice during grain filling are not well understood. In this paper, Zhehui7954 an excellent indica restorer line (wildtype) and its corresponding mutant (psf) with the premature senescence of flag leaves were used to study the effect of different N supplies in the alteration of physiological and biochemical components of flag leaf organ and its functions during grain filling. Results The results showed that the psf mutant appeared to be more susceptible to the varying N supply levels than WT. For instance, the psf mutant showed considerably lower Pn, Chl a, Chl b, and Car contents than its WT. N deficiency (LN) decreased leaves photosynthetic activities, N metabolites, but significantly burst O2 •−, H2O2, and relative conductivity (R1/R2) concentrations, which was consistent with the expression levels of senescence-associated genes. Sucrose, glucose, and C/N ratio concentrations increased with a decrease in N level, which was closely associated with N and non-structural carbohydrate translocation rates. Increases in POD activity were positively linked with the senescence-related enhancement of ROS generation under LN conditions, whereas, SOD, CAT, and APX activities showed opposite trends. High N (HN) supply significantly inhibits the transcripts of carbohydrate biosynthesis genes, while N assimilation gene transcripts gradually increased along with leaf senescence. The psf mutant had a relatively higher grain yield under HN treatment than LN, while WT had a higher grain yield under MN than HN and LN. Conclusions This work revealed that the C/N ratio and ROS undergo a gradual increase driven by interlinking positive feedback, providing a physiological framework connecting the participation of sugars and N assimilation in the regulation of leaf senescence. These results could be useful for achieving a higher yield of rice production by appropriate N supply and plant senescence regulation.